Integration of Technology in English Classroom Interaction - Basri D, Muhammad; Ampa, Andi Tenri; Andriani, Andi Arie; Asmasary, Andi Arwinny (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Technology has been determined to play a vital role in facilitating students’ learning of English as a foreign language in Indonesia. Thus, this study mainly highlights the need for integrating technology in the classroom, for example, using computer-based learning and networks and communications systems to support learning. In this way, classroom interaction can offer a new way for students to interact and engage with course materials. Furthermore, this study aimed to determine the students’ prior knowledge of technology in learning English, including their interests and usage; our findings also discuss how lecturers integrate technology in the classroom. This study used a descriptive quantitative method, with respondents including 60 students and 8 lecturers. The results of the research describe the students’ prior knowledge, the interest and use of technology in learning English, as well as the integration of technology used by the lecturers in classroom interaction. It can be concluded that most students and lecturers are not that all familiar with the 14 kinds of technology that are commonly used for English learning.